HOPES AND HURDLES OF DENDRIMERS FOR THE TREATMENT OF PARKINSON’S DISEASE - KHUSHI AGGARWAL; SHALU VERMA; ARJEETA SINGH RATHORE; TARUN PARASHAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Neurodegenerative conditions include Parkinson’s disease (PD), a prevalent movement disease marked by Lewy body aggregation in the midbrain and a gradual loss of dopamine neurons. It is the second most common neurological condition that progresses faster. The exact cause of this idiopathic condition is not known, while risk factors, such as aging, pesticide exposure, family history, and environmental pollutants are linked to it. Both motor and non-motor signs are displayed, such as bradykinesia, stiffness, stooping posture, and rest tremor. Additional symptoms of PD include autonomic and speech difficulties, cognitive impairment (dementia), and neurobehavioral disorders (depression). The only long-term and symptomatic treatments available for PD are inadequate. PD patients are challenging to treat medically because there are few PD medications available, and levodopa is the usual course of treatment. However, prolonged usage of levodopa results in dyskinesia. New treatments targeting pertinent targets in various diseases have been developed as a result of this challenge. Novel drug delivery systems are designed to prevent, diagnose, and treat various diseases while improving the overall efficacy of medications to overcome drawbacks, such as poor drug penetration in the brain, poor bioavailability, limited solubility, severe adverse effects, and long-term ineffectiveness. There are various novel approaches present for the treatment of different diseases, including liposomes, nanoemulsion, niosomes, dendrimers (DDs), and solid lipid nanoparticles. DDs have become viable substitutes for existing treatments. The unique polymeric structures known as DDs offer a versatile framework for creating a range of nanosystems that can be used to cure different diseases and ultimately improve the lives of millions of people worldwide. DDs have been suggested as intriguing drug delivery vehicles that can penetrate the blood–brain barrier and boost the bioavailability of traditional medications in the brain and genetic material by decreasing the synthesis of particular targets. They are also effective agents that block alpha-synuclein fibrillation and have anti-inflammatory qualities. In this review, we will talk about the novel drug delivery approach based on DD formulations and its recent advancements for the treatment of PD.